Digital communication strategies: An analysis of university websites in Latin America - Ulli Flores, Washington Edward; Solórzano Soto, Rita Magdalena (Revista Universidad de Guayaquil, 2023)
This research aimed to analyze the importance of university websites as strategies to strengthen digital communication, emphasizing its importance in relations with the public and identifying the structure of the selected web pages. The methodology used was based on a mixed analysis, both qualitative and quantitative. The inductive method was used, through the technique of research and content analysis. As an evaluation instrument, a file made up of 5 elements was designed based on the characteristics that constitute the communication and the evaluation report of the Nibbler online program was included. The results obtained allowed us to establish that none of the evaluated universities reached optimal levels in the application of the selected digital communication elements, thus showing that, at present, despite the effort to adapt to the changes driven by new technologies, there are still prevailing weaknesses in the environment of this institutional area. Therefore, these websites require the strengthening of their communication strategies
Keywords: Websites; Latin American universities; digital communication; communication strategies; relationship with the public